Exploring trust: culturally responsive and positive school leadership. Issue 3 (25th October 2021) - Banwo, Bodunrin O.; Khalifa, Muhammad; Seashore Louis, Karen
Abstract : Purpose: This article explores the connection between Culturally Responsive School Leadership (CRSL) and Positive School Leadership (PSL) and how both engage with a concept that deeply connects both leadership expressions – trust. Design/methodology/approach: A multi-year, single site case study method examined a district-level equity leader, and her struggles and successes with promoting equity and positive culture throughout a large suburban district in the US. Findings: Trust, established through regular interactions, allowed the district's leadership equity team to build positive relationships with building leaders. Trust was not only a mitigating factor on the relationships themselves, but also regulated the extent to which equitable practices were discussed and implemented in the district. Trust allowed conflicts to surface and be addressed that led to individual and organizational change. Research limitations/implications: The case highlights the importance of both CRSL and PSL principals, along with the idea of "soft power" in cultural change, to foster equity in schools. Established trust does not erase the difficulties of enacting CRSL/PSL, but allows the difficulties to be addressed. The authors found that dynamic, iterative, regular interactions over a long period reinforced trust allowed CRPSL to take root in the district. Originality/value: The authors use a single subject case to argue that the core of empirical work moving forward should draw on an integration of culturally responsive leadership.